COMPARATIVE RESEARCH REGARDING THE DESIGN AND THE DEVELOPMENT OF THE G CODE PROGRAMMING LANGUAGE BETWEEN CASE R290-02IS AND THE CLASSIC VERSION, CONSTITUENTS OF THE GARLAND PRODUCT C3G 1200, 1400, 1600 - Valeria Victoria IOVANOV (Fiabilitate şi Durabilitate)
A CNC machine makes use of mathematics and various coordinate systems to understand and process the information it receives to determine what to move where and how fast . The most important function of any CNC machine is precise and rigorous control of the movement. All CNC equipment have two or more directions of motion, called axes. CNC machines are driven by computer controlled servo motors and generally guided by a stored program, the type of movement (fast , linear, circular ) , the moving axes, the distances of movement and the speed of movement ( processing ) being programmable for most CNC machines . This paper proposes the design and implementation of a G code programming language for the reference point Case R290 - 02IS the short version compared to the classical part of the garland product C3G 1200,1400,1600 , reference points used in all fields that use conveyors .